2022
DOI: 10.1186/s12913-022-07782-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated, cross-sectoral psycho-oncology (isPO): a new form of care for newly diagnosed cancer patients in Germany

Abstract: Background The annual incidence of new cancer cases has been increasing worldwide for many years, and is likely to continue to rise. In Germany, the number of new cancer cases is expected to increase by 20% until 2030. Half of all cancer patients experience significant emotional and psychosocial distress along the continuum of their disease, treatment, and aftercare, and also as long-term survivors. Consequently, in many countries, psycho-oncological programs have been developed to address this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 146 publications
0
29
0
Order By: Relevance
“…In Germany, the integrated, cross-sectoral psycho-oncological care programme ‘isPO’ was designed, implemented and evaluated between 2017 and 2022 (Jenniches et al 2020 ). The programme is offered to newly diagnosed adult cancer patients for 12 months, parallel to their biomedical treatment (Kusch et al 2022 ). On an individual level, isPO aims to reduce patients’ symptom severity of their depression and anxiety; on a system level, it offers a needs-driven psycho-oncological care programme for comprehensive implementation into nationwide cancer care (Jenniches et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Germany, the integrated, cross-sectoral psycho-oncological care programme ‘isPO’ was designed, implemented and evaluated between 2017 and 2022 (Jenniches et al 2020 ). The programme is offered to newly diagnosed adult cancer patients for 12 months, parallel to their biomedical treatment (Kusch et al 2022 ). On an individual level, isPO aims to reduce patients’ symptom severity of their depression and anxiety; on a system level, it offers a needs-driven psycho-oncological care programme for comprehensive implementation into nationwide cancer care (Jenniches et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The integrated approach proposed in the FRIPOS project seems to be an adequate response to the claims that appear in the literature related to the concept of holistic management [44,45] and joins the studies that have already demonstrated its effectiveness and importance [46][47][48]. Indeed, the inclusion of the psycho-oncologist in the treatment has brought significant benefits or at least a state of stability in many areas (in contrast to what happened in the group TAU), especially in relation to several aspects highlighted in the literature: the development of symptomatic manifestations related to psychopathology as a result of or during the journey against cancer and the indices of psychological functioning, especially at the emotional level [49].…”
Section: Discussionmentioning
confidence: 85%
“…31 The programme is offered to newly diagnosed adult cancer patients for 12 months, parallel to their biomedical treatment. 32 On an individual level, isPO aims to reduce patients' symptom severity of their depression and anxiety; on a system level, it offers a needsdriven psycho-oncological care programme for comprehensive implementation into nationwide cancer care. 31 The programme was implemented in January 2019 in four specially established psychooncological care networks in North Rhine-Westphalia, Germany.…”
Section: Settingmentioning
confidence: 99%